Pengembangan Media Pembelajaran Berbasis Gamification Bagi Siswa SMK Keminatan RPL (Studi Kasus : SMKN 5 Malang) - Achmeddieo Maulana; Denny Sagita Rusdianto; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Current technological developments have reached all fields including education. With the support of technology, teaching and learning activities can be better. State Vocational School 5 Malang has sufficient facilities in terms of technology, but these facilities have not been fully utilized for teaching and learning activities. In this research, an e-learning application that has a discussion forum feature is developed to carry out the discussion process outside of teaching and learning activities. The development of this e-learning application uses the gamification approach so that it can attract the attention of students to continue to use the e-learning. The system development process is done using the waterfall method. The developed system has 52 functional needs and 1 non functional requirement. Functional requirements testing is done that is testing black box and white box with 100% valid results. Non-functional requirements testing is done that is compatibility testing with the results of 5 critical issues on the browser. Based on the results obtained in this study, it can be concluded that the e-learning discussion forum for programmers in RPL subjects using the gamification approach can be used as a learning medium that will help during the teaching and learning process and also makes it easier for teachers to provide material outside of these class hours.